Integration Of Non-Material and Material Tools In Islamic Education: The Role Of Social Interaction, Authority, Punishment, And Learning Tools and Media - Wahyuni Nurdin; Syarifuddin Ondeng; Muhammad Yahdi (CV PUTRA PUBLISHER, 2025)
Educational tools play a strategic role in supporting the success of Islamic education. Educational tools are not limited to material aspects such as facilities and learning media, but also include non-material aspects such as social interaction, teacher authority, and educational punishment. This study aims to examine the concept of Islamic educational tools and to describe the forms of material and non-material educational tools from the perspective of Islamic educational thought. This research employs a library research method by analysing books and academic journals relevant to the research topic. Data were collected through documentation techniques and analysed using data collection, data reduction, data display, and data verification stages. The findings indicate that Islamic educational tools encompass all facilities, actions, and situations that are consciously utilised to achieve the objectives of Islamic education, namely forming individuals who are faithful, pious, knowledgeable, and possess noble character. Islamic educational tools are classified into two categories: material tools, including educational facilities and learning media, and non-material tools, including social interaction, teacher authority, and educational punishment. Both types of educational tools complement each other and play an essential role in shaping students' holistic personality.